Pandangan Manuel Velasquez Mengenai Masalah Korupsi dalam Bisnis Global - Alois A. Nugroho (Respons: Jurnal Etika Sosial, 2008)
In the domain of public administration, corruption is one of many problems against which some countries in the world still had to struggle. In the domain of business administration, it is one of the dilemmas that shadows the operation of multinational corporations around the globe. This article analyzes the position taken by Manuel Velasquez in his article “Is Corruption Always Corrupt?”, in which Velasquez tries to avoid “moral absolutism” by evaluating corruption not “from outside”, but “from within” any given culture. The article tells us that “corruption” occurs in the context of “competitive state”, “patrimonial state”, “personalized state”, “neo-patrimonial state”. Finally, this paper concludes with the position that, be apparently very sympathetic as it may, Velasquez’s position cannot solve MNC’s dilemma posed by the very problem of corruption.